Rainfall and High Humidity Influence the Seasonal Dynamics of Spores of Glomerellaceae and Botryosphaeriaceae Genera in Avocado Orchards and Their Fruit Rot Association - Lorena Tapia; Diyanira Castillo-Novales; Natalia Riquelme; Ana Luisa Valencia; Alejandra Larach; Ricardo Cautín; Ximena Besoain (Agronomy, 2025)
Avocado, a fruit consumed worldwide and essential for countries like Mexico and Chile, faces significant postharvest challenges, particularly during prolonged storage and transportation periods, where Botryosphaeriaceae and Glomerellaceae genera cause fruit rots that can generate substantial economic losses. This study investigated three Hass avocado orchards in the Valparaíso region of Chile to identify spore dispersion peaks, analyze the aerial dynamics of fungal inoculum, and evaluate the association with climatic conditions, as well as the incidence (I) and damage index (DI) of fruit rots. Spore traps were installed in symptomatic trees and monitored weekly over 13 months. Meteorological data were collected in parallel. Fruits from these orchards were sampled to evaluate postharvest rots, physiological maturity, and disease severity using molecular techniques, including DNA sequencing and phylogenetic analysis of isolated pathogens. The results revealed that spore peaks for both fungal families were closely associated with increased rainfall and high relative humidity, particularly from June to mid-September (winter season). The Santo Domingo orchard exhibited the highest disease pressure, with stem-end rot reaching an I of 44% and a DI of 17.25%, and anthracnose reaching an I of 23% and a DI of 12.25%. This study provides the first long-term, field-based evidence of airborne spore dynamics of Botryosphaeriaceae and Glomerellaceae in Chilean avocado orchards and their statistical relationship with environmental variables. These findings highlight the potential of incorporating climatic indicators—such as rainfall thresholds and humidity levels—into monitoring and early-warning systems to optimize fungicide application timing, reduce unnecessary chemical use, and improve postharvest disease management in avocado production.